Factors Affecting Customer Satisfaction Facebook User in DKI Jakarta - Salsabila, Adiba Rizka; Satya, Irma; Suryawardana, Edy (Economics and Business Solutions Journal, 2022)
this study aims to determine the effect of product, trust, price, convenience, and experience on customer satisfaction for Facebook users in DKI Jakarta. The discussion described in this study is about purchases on social commerce Facebook. The data used in this study are primary and secondary data. Primary data was obtained from collecting questionnaire responses using 5 Likert scales as a measurement of research variables and secondary data obtained from various reliable sources. This research uses non-probability sampling method with purposive sampling technique. The researcher uses the Confirmatory Factor Analysis (CFA) analysis method using the AMOS version 26 program which is part of the Structural Equation Model (SEM). Research on 175 Facebook users in DKI Jakarta illustrates that trust is a very important factor in transactions on the Facebook marketplace platform. The transaction experience passed by the respondent can also be used as a factor in influencing customers to feel satisfied. Product, price, and convenience have no influence on customer satisfaction when buying goods on the facebook marketplace